Indicators of Airway Secretion Weight in Mechanically Ventilated Subjects - Ntoumenopoulos, George; Berry, Marc P; Camporota, Luigi; Lam, Lawrence (Respiratory care, 2019)
Clinicians may use adventitious breath sounds on lung auscultation and a "sawtooth" pattern on the ventilator expiratory flow waveform as indicators of the need for chest physiotherapy for airway-secretion clearance in mechanically ventilated patients. This study seeks to identify potential clinical and novel indicators of the weight of airway secretions cleared from a single session of chest physiotherapy in mechanically ventilated subjects. We recorded airway crackles using artificial airway acoustic sound monitoring and computerized lung-sound amplitude using artificial airway acoustic sound detection and compared them to standard clinical assessments in 71 mechanically ventilated subjects immediately prior to a single session of chest physiotherapy. Correlational analyses were undertaken between the weight of airway secretions obtained after the single session of chest physiotherapy as the dependent variable and novel assessments, clinical assessments, patient characteristics, and ventilator parameters as the independent variables. Multiple linear regression analyses were then used to determine the best model to predict the weight of airway secretions obtained from the single chest physiotherapy session. Data are reported as mean and median as appropriate. Significance was set at < .05. 71 mechanically ventilated subjects were included for analysis. Statistically significant associations with the weight of airway secretions included the presence of a sawtooth waveform on expiration and the novel assessment of average airway crackles during inspiration. The best predictive model of the weight of airway secretions included the presence of the sawtooth waveform on expiration and ventilator tidal volume. Simple clinical assessments used in this study were able to independently predict the weight of airway secretions cleared during a single session of chest physiotherapy. The novel assessments used in this investigation did not add any further value.